A 4 mm toroidal microtransformer built with wire bonding and MCM technologies - Nascimento, Fellype do; Telles, Antonio C. C.; Rocha, Marinalva M.; Teixeira, Ricardo C. (2019 34th Symposium on Microelectronics Technology and Devices (SBMicro), 2019)
Manufacturing of small-scale magnetic devices is a subject that is not yet fully consolidated. Then the development process - design, fabrication and characterization - of microtransformers continues as object of studies for several applications. In this work it is presented the development and characterization steps of a four mm diameter toroidal microtransformer built using wire bonding and MultiChip Module (MCM) technologies. The device has a 19:1 turn ratio, with 31 μm diameter aluminum wire bond around the top of a MnZn ferrite core. The wire bonds are connected to thin film gold tracks with ~3.5 μm thickness at the bottom in order to complete the windings. The main parameters measured were the inductances and resistances of primary and secondary windings, and also the series-aiding and series-opposing inductances, all of them in the frequency range from 10 kHz to 2 MHz. With the results from those measurements the quality factors, mutual inductance and coupling coefficients were obtained. The inductance values of both windings are in agreement with expected ones. The device shows a good coupling coefficient and acceptable quality factors. The results show that it is feasible to build microtransformers with wire bonding onto an MCM substrate.